SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN KETUA RT/RW BERBASIS WEB MVC MENGGUNAKAN METODE TOPSIS (Studi Kasus: RT.02/RW.09 Griya Satria Bukit Permata Purwokerto) - Tirtayasa, Arta; Yeri Kristiyanto, Daniel (Jurnal Teknoif Teknik Informatika Institut Teknologi Padang, 2023)
The election of the chairman of the Neighborhood Unit (RT)/(RW) is one of the democratic mechanisms carried out by the community at the RT/RW level to determine who will lead  of the community in the neighborhood where they live. Each (RT) and (RW) is led by the RT Chair and RW Chair. However, the process of selecting the head of the RT/RW Griya Satria Bukit Permata is still carried out by deliberation. A decision support system (DSS) is needed that can help the process of selecting RT/RW heads using the web-based Model-View-Controller (MVC) Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) method. Selection is carried out by analyzing and selecting the best candidates based on criteria namely loyalty, leadership, integrity, age and experience. The aim of this research is to create a DSS for the selection of RT/RW heads based on the TOPSIS method to assist in the selection of prospective RT/RW heads. The results of implementing can seek recommendations for candidates for RT/RW heads in an objective, directing a process for selecting RT/RW heads. Namely, with the result of Candidate A's preference value 0.896, Candidate B 0.756, C 0.477, D 0.432 and E 0.463. DSS for the selection of RT/RW heads using the TOPSIS method is suitable and can determine the results of the ranking of the five head candidates and five criteria and the implementation of DSS using the MVC TOPSIS method can work well to find out and make decisions about the RT/RW head candidates.